PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA KOPERASI PINANG SARI KABUPATEN BADUNG - I Gusti Ayu Putri Darmayanti; I Wayan Mendra; Tjok Istri Sri Harwathy (VALUES, 2022)
The problem that exists in the Pinang Sari Cooperative in Badung Regency is a significant decrease in the percentage of SHU profits that occurred in 2020 due to the Covid-19 pandemic, high employee absenteeism and employees always arriving late. The low self-compensation, work discipline, and motivation in the Pinang Sari Cooperative, Badung Regency. This study aims to determine the effect of compensation, work discipline, and motivation on employee performance at the Pinang Sari Cooperative, Badung Regency. This research was conducted at the Pinang Sari Cooperative, Badung Regency using a population and a sample of 38 employees as research respondents. The sampling technique used in this research is the census method. Data was collected through interviews and questionnaires. The data analysis technique used in this study is multiple linear regression analysis which is processed using SPSS version 23 software. Based on the results of the analysis, this study shows that compensation, work discipline and motivation partially have a positive and significant effect on employee performance at the Pinang Sari Cooperative, Badung Regency .